The combined effect of water status and crop level on Tempranillo wine volatiles. (18th August 2016) - Talaverano, Inmaculada; Valdés, Esperanza; Moreno, Daniel; Gamero, Esther; Mancha, Luis; Vilanova, Mar
Abstract: BACKGROUND: The effect of water status and crop level on the volatile composition of Tempranillo wine was investigated over two growing seasons (2010–2011) in Extremadura (Spain). Three water status treatments (T0, Rainfed control; T1, Early regulated deficit irrigation; T2, Late regulated deficit irrigation) were combined with two crop levels treatments (TH, cluster thinning; C, control). RESULTS: Crop level treatment had a higher effect on individual volatiles analyzed in Tempranillo wine than water status. The combinations of water status and crop level treatments showed effects on all families of compounds with the exception of acetates and volatile fatty acids. Alcohols, C6 compounds and phenol volatiles produced the highest concentrations at the lower level of available water and when cluster thinning was applied (T0–TH). However, ethyl ester and lactones showed higher concentrations in regulated deficit irrigation (T1 and T2) and when cluster thinning was not applied. CONCLUSION: The combined effect of rainfed and cluster‐thinning treatments (T0–TH) increased the majority of individual aromatic compounds quantified in Tempranillo wines and also showed the highest total odor activity value. © 2016 Society of Chemical Industry